Mycobiota and identification of aflatoxin gene cluster in marketed spices in West Africa - Gnonlonfin, G.J.B.; Adjovi, Y.C.S.; Tokpo, A.F.; Agbekponou, E.D.; Ameyapoh, Y.; Souza, C. de; Brimer, L.; Sanni, A. (Elsevier, 2013)
Fungal infection and aflatoxin contamination was evaluated on 114 samples of dried and milled spices such as ginger, garlic and black pepper from southern Benin and Togo collected in November 2008-January 2009. These products are dried to preserve them for lean periods available throughout the year. Fungal contamination was evaluated after plating on selective media with a total of 20 fungal genera identified, ranging from 7 in garlic to 14 in ginger. Ginger and pepper showed high incidence of fungal contamination compared to garlic that had lower levels of fungal contamination. Species of Aspergillus were dominant on all marketed dried and milled spices irrespective of country. Gene characterization and amplification analysis showed that most of the A. flavus isolates possesses the cluster genes for aflatoxin production. Aflatoxin B1 assessment by Thin Layer Chromatography showed that only garlic (1 sample) and ginger (4 samples) were naturally contaminated with aflatoxin B1 ranging from 390 μg/kg to 1045 μg/kg respectively. Previous reports have mostly highlighted the risk of mycotoxin exposure from staple crops and vegetables in Africa, but such risks now need to be evaluated further for other products such as dried and milled spices.